Pensar en español desde América. El ensayo como escritura de una independencia inconclusa - Aínsa, Fernando (Philologia Hispalensis, 2011)
Since the earliest times of Latin American Independence, there are obvious efforts to ensure that the political emancipation would be followed by a liberation of the mentalities. The aim is to “invent” an “original” thought (Simón Rodríguez) and to develop an own, deeply rooted philosophy, based on the “needs” of each period and each country ( Juan Bautista Alberdi), foreign to any “vassalage” (Esteban Echevarría) and claiming the autonomy of Amer- ican culture (Andrés Bello). Essays will be the privileged tools for this search.